LOCAL INTERPRETATION OF THE ARCHIPELAGO AND PRESERVATION OF CULTURAL IDENTITY: EPISTEMOLOGICAL AND CULTURAL ANALYSIS AND REVITALIZATION STRATEGIES IN THE ERA OF GLOBALIZATION - Fathoni, Ahmad Nur; Hakim, M. Luqman; Cahyono, Agung Mandiro; Mukti, Anwar; Bahrudin, Moh.; Evannathan, M. Farrel (West Science Islamic Studies, 2025)
This study analyzes the role of local interpretations in the preservation of cultural identity and the urgency of their revitalization amid the currents of globalization and homogenization of religious interpretations. Using a descriptive qualitative approach based on literature review, this study examines Javanese, Sundanese, and Bugis interpretations; scientific articles related to vernacularization; and manuscripts and supporting documents on the development of local interpretations. The results show that local interpretations have distinctive epistemological and methodological characteristics through the integration of the Qur'anic text with cultural values, linguistic idioms, and the social structure of the local community. This tradition not only functions as a medium for religious understanding, but also as a vehicle for preserving regional languages, local scripts, and the formation of a grounded Islamic identity. However, the dominance of Middle Eastern interpretations, limited access to manuscripts, and a lack of regeneration of Islamic scholars pose serious challenges to the sustainability of local interpretations. This study offers revitalization strategies through manuscript digitization, curriculum integration, production of new works in regional languages, and collaboration in research and cultural activities. Thus, local interpretations are positioned as an important pillar of Islamic plurality in the archipelago as well as a foundation for the preservation of the nation's intellectual and cultural heritage.